The Effects of Intrinsic and Extrinsic Reading Motivation on Reading Performance in Elementary School. Issue 1 (1st January 2022) - Kanonire, Tatjana; Lubenko, Jelena; Kuzmina, Yulia
ABSTRACT: Reading motivation is an important factor that can predict reading performance in elementary school. The present study aimed to investigate whether reading motivation could mediate the relationship between reading skills at the beginning of school and reading performance in the middle of elementary school. Longitudinal data from 979 students (52% girls) in Russia were used. Data on early reading skills in Grade 1 and reading comprehension and reading motivation in Grade 3 were collected. The results indicated that intrinsic and extrinsic motivation in Grade 3 predicted reading performance in Grade 3 after controlling for reading skills in Grade 1. A two-level multilevel mediation analysis showed that intrinsic motivation did not mediate but extrinsic motivation partly mediated the effect of reading skills in Grade 1 on subsequent reading performance. The results are discussed in light of previous studies. Suggestions for future research and practical implications are also discussed.